A Facile Synthesis of Graphene-WO3 Nanowire Clusters with High Photocatalytic Activity for O2 Evolution. (24th July 2014) - Zhou, M.-J.; Zhang, N.; Hou, Z. H.
Abstract : In the present work, graphene-WO3 nanowire clusters were synthesized via a facile hydrothermal method. The obtained graphene-WO3 nanowire clusters were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FT-IR), Raman spectroscopy, and ultraviolet-visible diffuse reflectance spectroscopy (DRS) techniques. The photocatalytic oxygen (O2 ) evolution properties of the as-synthesized samples were investigated by measuring the amount of evolved O2 from water splitting. The graphene-WO3 nanowire clusters exhibited enhanced performance compared to pure WO3 nanowire clusters for O2 evolution. The amount of evolved O2 from water splitting after 8 h for the graphene-WO3 nanowire clusters is ca. 0.345 mmol/L, which is more than 1.9 times as much as that of the pure WO3 nanowire clusters ( ca. 0.175 mmol/L). The high photocatalytic activity of the graphene-WO3 nanowire clusters was attributed to a high charge transfer rate in the presence of graphene.